Clinical trials market: state and prospects, IT segment - Bitkova, T.; Kalnitsky, R. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The article provides an overview of the development of the global and Ukrainian clinical trials market and indicates that the field of clinical research is very promising and its development correlates with the development of technologies in the world, which in turn are developing quickly and successfully. The COVID-19 pandemic has shown that global pharmaceuticals, applying the best clinical research methods, are able to find effective solutions in very short periods of time. The market is stable, because it refers to the protection of human health. According to forecasts, the clinical trials market will grow along with the growth of investments in it. Ukraine has a good medical base with a large infrastructure and a fairly developed IT sector, which makes it promising to open contract research organizations (CROs) in the country, in particular, those specialized in statistical analysis of research and clinical programming. A large number of CROs, including those in Ukraine, cooperate with large sponsors-corporations, which are mostly foreign ones. This helps develop the domestic economic market and provides a high level of income for employees, because the industry is highly specialized and high-tech. The authors offer a basic model of IT project dynamics, which reflects the process of its implementation and allows displaying the dynamics of various indicators (given the total number of project tasks). The object of simulation is a newly established IT firm (startup), and a typical project faced by a statistical CRO is considered. The model can be used for planning short-term or long-term activities of the firm in the field of clinical research. Since the market and the field of clinical research as a whole is developing and growing, starting one’s own CRO with statistical specialization can be considered as a promising business in Ukraine.